Global, regional, and national burden of chronic kidney disease due to diabetes mellitus type 2 from 1990 to 2021, with projections to 2036: a systematic analysis for the Global Burden of Disease Study 2021 - Hu, Ruikang; Zhao, Zhifeng; Xie, Luze; Ma, Zhenjie; Wu, Wen; Li, Shuangxi (Frontiers in Medicine, 2025)
BackgroundChronic kidney disease (CKD) due to type 2 diabetes mellitus (T2DM) has emerged as a significant global health burden, with rising incidence and prevalence rates observed over the past decades.MethodsWe utilized the latest data from the Global Burden of Disease Study (GBD) 2021. Firstly, we reported the number of incidence, prevalence, deaths, and Disability-Adjusted Life Years (DALYs) attributed to CKD due to T2DM, accompanied by their respective Age-Standardized Rates (ASRs), for the year 2021. This analysis encompassed a global perspective and was further stratified by various subtypes. Moreover, we examined trends globally and within specified sub-types to investigate the temporal dynamics of the ASRs. We estimated the percentage change in ASRs, providing a quantitative measure of the rate of change in the burden over the study period. Moreover, we utilized the Bayesian age-period-cohort (BAPC) model to forecast the future burden.ResultsGlobally, the ASRs of CKD due to T2DM all have witnessed a notable rise except for age-standardized prevalence rate (ASPR). The trends observed in both sexes and nearly all age groups were found to be congruent with those of the overall population. The increase in disease burden being greatest in the middle and lower SDI regions. The predicted results showed that the ASRs would still increase from 2022 to 2036.ConclusionThis study highlights the critical importance of addressing the growing burden of T2DM-related CKD on global health. Effective prevention and management strategies, including improvements in diabetes care, renal health promotion, and access to healthcare services, are urgently needed to mitigate the future impact of T2DM-related CKD.